Pengaruh Model Pembelajaran Inkuiri Terbimbing Terhadap Kemampuan Pemecahan Masalah Peserta Didik Kelas XI MIA di SMAN 11 Makassar (Studi Materi Pokok Laju Reaksi) - Palajukan, Yulianti; Sugiarti, Sugiarti; Herawati, Netti (Jurusan Kimia FMIPA UNM, 2021)
This study is a quasi-experimental research (Quasi Experiment) that aims to determine the effect of guided inquiry learning model to the problem-solving ability of students Class XI SMAN 11 Makassar. The study design used was